Rompendo silêncios: narrativas afrodescendentes no Brasil e na Alemanha - de Jesus, Jessica Oliveira (Revista Leitura, 2019)
O presente texto faz uma breve análise comparativa entre produções literárias negras em língua alemã e em língua portuguesa do Brasil. O foco da análise é o afronte à estratégia colonial do silenciamento, imposto ao povo negro em diáspora, operado na obra da poeta e ativista afro-alemã May Ayim e da romancista afro-brasileira Ana Maria Gonçalves. Trataremos da literatura da diáspora africana como ferramenta que “estilhaça a máscara do silêncio” (EVARISTO, 2017), tanto na obra Um defeito de cor (2006), de Gonçalves, como na poesia afro-alemã de May Ayim e de sua tradução no Brasil, traçando paralelos e diálogos entre a literatura negra brasileira e a negra alemã Breaking the silence: afrodescendant narratives in Brazil and in German The present text is a brief comparative analysis between Black literary productions in German and Brazilian Portuguese. The focus of the analysis is the defiance of the colonial strategy of silencing, inflicted on Black people in the diaspora, which can be seen in the work of the Afro-German poet and activist May Ayim and of the Afro-Brazilian novelist Ana Maria Gonçalves. We will deal with African Diaspora Literature as a tool that “shatters the mask of silence” (EVARISTO, 2017), both in Gonçalves's Um defeito de cor (2006), and in Ayim’s Afro-German poetry and its translation into Brazilian Portuguese, drawing parallels and dialogues between Black Brazilian literature and the Black German Literature. Keywords: Black Brazilian Literature. Black German Literature. Afrodiasporic Literature. Ana Maria Gonçalves. May Ayim DOI: 10.28998/2317-9945.2019n63p247-259